Otuđiva i neotuđiva posvojnost u hrvatskome jeziku - Matasović, Ranko (Array, 2002)
The distinction alienable vs. inalienable possession is not grammaticalized in Croatian, since the same constructions can be used to express both types of possession. However, this typologically well attested distinction can be expressed in Croatian as well, if one takes into account that certain constructions (such as dative of possession) are pragmatically favored by the constructions with inalienably possessed NPs. With respect to this, Croatian is similar to many other languages of Central Europe, such as German, and very different from the peripheral languages, such as English or Irish.